The day of week effect on financial companies among financial sector in Kuala Lumpur composite index (KLCI) - Chin, Pea Lee (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The global financial crisis currently is a latest crisis in the field of financial market. The preliminary evidence indicates that Efficient Market Hypothesis (EMH) might have been misplaced due to various anomalies. In Malaysian stock market, the existence of DOW effect is relatively less consistent and relatively little research conducted on market anomalies especially those concerning the DOW effect. The day-of-the-week (DOW) effects in the eight financial companies of Kuala Lumpur Composite Index CKLCI) using stock return data of individual financial companies conducted in the study. The study covering period from 2004 to 2011 and discovers the financial companies are highly efficient according the DOW effect. The study discovers the lowest mean returns of overall during entire period of global financial crisis oQ. Monday for five fmancial companies out of eight financial companies. There is impact of global financial crisis on the studied sample.